FRUIT SWEETNESS CHARACTERIZATION USING IMPEDANCE SPECTROSCOPY METHOD - Rahmondia N Setiadi; Lazuardi Umar (Spektra: Jurnal Fisika dan Aplikasinya, 2019)
The processing of agricultural products requires technology implementation to increase its production. One way of this technology implementation to increase the production is fruit sweetness measurement, which can be used as a sorting tool of fruit products. The sorting process using this tool can be done with easier way compare than the manual and destructive test. The fruit sweetness is composed of a mixture of sweet molecules fructose, glucose, and sucrose. The measurements of these molecules are usually done with four-point probe and use dc current. In this study, a fruit sweetness characterization using impedance spectroscopy method has been developed and realized, which uses an ac current. By using this method, fruit sweetness level can be characterized based on the impedance measurement on the flesh of a test fruit based on its dielectric properties. The obtained characterization results show that the fruit sweetness level can be measured by the impedance measurement. The obtained impedance is proportional to the concentration of the sweet molecule glucose. This method can characterize the fruit sweetness well and agrees with the calibration result. Therefore, this method can be used to increase agricultural products.